Feasibility and Income of Milk Fish Business in Bandar Batauga Sub-District, Buton South District - Hamar, Bahtiar; Failu, Ismail; Cahyani, Wa Ode Siti; Sirza, L. M. Junaidin (Jurnal Media Akuakultur Indonesia, 2023)
Bandar Batauga Village is one of the areas in Batauga District, South Buton Regency, based on data on the number of local residents who earn their living as fish farmers. The pond area in Bandar Balauga Village which is used for pond cultivation is approximately 4 hectares more than the potential pond area of 18 hectares in Batauga District. Based on a survey, it was found that there were 40 traditional fish farmers using a polyculture system who cultivated milkfish. The aim of the research is to determine the income of the milkfish business in Bandar Batauga Village, Batauga District, South Buton Regency. And to find out if the milkfish business in Bandar Batauga Village, Batauga District, South Buton Regency is worth pursuing. The research was carried out in Bandar Batauga Village, Batauga District, South Buton Regency. The results of the research show that the population of Bandar Batuga sub-district in 2020 is 1200 people consisting of 661 men, 539 women with 310 heads of families. The majority of the population is of productive age (12-60 years), namely around 920 people. The population aged 0-23 years is 520 people or 43.33% of the population aged up to 24-47 years is 300 people or the population aged 48-70 years is 380 people. Milkfish production with total fixed costs m per season is IDR 250,000. variable costs 36,000 000. Total production costs 36,250,000. The income of milkfish farmers is IDR. 33,750,000 in 1 production season. The conclusion of this activity is an analysis of the milkfish farming business based on the R/C Ratio, so a calculation of 1.9 is obtained. This value shows every cost incurred by RP. I or provide revenue of 1.9, thus the milkfish business is worth pursuing and developing.